Association Between Smoking Cessation Treatment and Healthcare Costs in a Single-Payer Public Healthcare System. Issue 1 (6th July 2022) - Baliunas, Dolly; Voci, Sabrina; de Oliveira, Claire; Selby, Peter; Kurdyak, Paul; Rosella, Laura; Zawertailo, Laurie; Fu, Longdi; Sutradhar, Rinku
Abstract: Introduction: There has been little investigation of whether the clinical effectiveness of smoking cessation treatments translates into differences in healthcare costs, using real-world cost data, to determine whether anticipated benefits of smoking cessation treatment are being realized. Aims and Methods: We sought to determine the association between smoking cessation treatment and healthcare costs using linked administrative healthcare data. In total, 4752 patients who accessed a smoking cessation program in Ontario, Canada between July 2011 and December 2012 (treatment cohort) were each matched to a smoker who did not access these services (control cohort). The primary outcome was total healthcare costs in Canadian dollars, and secondary outcomes were sector-specific costs, from one year prior to the index date until December 31, 2017, or death. Costs were partitioned into four phases: pretreatment, treatment, posttreatment, and end-of-life for those who died. Results: Among females, total healthcare costs were similar between cohorts in pretreatment and posttreatment phases, but higher for the treatment cohort during the treatment phase ($4, 554 vs. $3, 237, p < .001). Among males, total healthcare costs were higher in the treatment cohort during pretreatment ($3, 911 vs. $2, 784, p < .001), treatment ($4, 533 vs. $3, 105, p < .001) and posttreatment ($5, 065 vs. $3, 922, p = .001) phases. End-of-life costs did not differ. Healthcare sector-specific costs followed a similar pattern. Conclusions: Five-year healthcare costs were similar between females who participated in a treatment program versus those that did not, with a transient increase during the treatment phase only. Among males, treatment was associated with persistently higher healthcare costs. Further study is needed to address the implications with respect to long-term costs. Implications: The clinical effectiveness of pharmacological and behavioral smoking cessation treatments is well established, but whether such treatments are associated with healthcare costs, using real-world data, has received limited attention. Our findings suggest that the use of a smoking cessation treatment offered by their health system is associated with persistent higher healthcare costs among males but a transient increase among females. Given increasing access to evidence-based smoking cessation treatments is an important component in national tobacco control strategies, these data highlight the need for further exploration of the relations between smoking cessation treatment engagement and healthcare costs.